Peasants under siege : - Gail Kligman and Katherine Verdery. (Princeton University Press)
Laying the groundwork -- The Soviet blueprint -- The village community and the politics of collectivization, 1945-62 -- Creating party cadres -- Pedagogies of power : technologies of rural transformation -- Pedagogies of knowledge production and contestation -- Pedagogies of persuasion -- Fomenting class war -- Outcomes -- The collectives are formed -- The restratification and bureaucratization of rural life -- Conclusion -- Appendix I. Project and participants -- Appendix II. Methodology -- Appendix III. List of interviewers and respondents.